Harmoni Agama dan Budaya Bugis dalam Tiga Praktik Pengobatan Tradisional pada Naskah Tahṣīlul Fawāid - Sitti Arafah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This paper aims to describe and interpret the content of the Tahṣīlul Fawāid text, related to the harmonious encounter between religion and community culture in medicine as in the Tahṣīlul Fawāid text. The philological approach used in this paper uses a single manuscript edition. Transliteration and translation are steps taken to understand the content of the manuscript. The results show that the Tahṣīlul Fawāid Manuscript is one of the manuscripts written in the Bugis language. The manuscript consists of forty-five chapters, 18 of which are chapters related to medical practice, namely treatment with verses from the Qur'an, amulets, and herbal plants. The contents of the Tahṣīlul Fawāid manuscript cannot be separated from the cultural context of the community in relation to Islamic values ​​that are harmoniously intertwined. In addition, the practice of traditional medicine in the text has now been practiced by health workers while treating their patients. Keywords: Bugis culture, Medical practice, Religious harmony, Tahṣīlul Fawāid Tulisan ini bertujuan mendiskripsikan dan menginterpretasikan kandungan naskah Tahṣīlul Fawāid, terkait pertemuan harmoni antara agama dan budaya masyarakat dalam pengobatan sebagaimana dalam naskah Tahṣīlul Fawāid. Pendekataan filologi yang digunakan dalam tulisan ini menggunakan edisi naskah tunggal. Adapun transliterasi dan penerjemahan menjadi langkah yang dilakukan untuk memahami kandungan naskah. Hasil tulisan menunjukkan bahwa naskah Tahṣīlul Fawāid merupakan salah satu naskah yang ditulis dalam bahasa Bugis. Naskah terdiri dari empat puluh lima bab, 18 bab di antara merupakan bab terkait praktik pengobatan, yakni pengobatan dengan ayat-ayat Al-Qur’an, azimat, maupun tanaman herbal. Isi naskah Tahṣīlul Fawāid, tidak dapat dipisahkan dengan konteks budaya masyarakat kaitannya dengan nilai-nilai keislaman yang terjalin secara harmoni. Di samping itu, praktik pengobatan tradisional dalam naskah, saat ini telah dipraktikkan oleh para tenaga-tenaga kesehatan ketika sedang mengobati pasiennya. Kata Kunci: Budaya bugis, Harmoni agama, Praktik pengobatan, Tahṣīlul Fawāid